2009
DOI: 10.1111/j.1365-2044.2009.06168.x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of anatomical variations that can cause inadvertent dural puncture when performing caudal block in Koreans: a study using magnetic resonance imaging

Abstract: SummaryThe purpose of this study was to investigate the prevalence of the anatomical abnormalities that can induce inadvertent dural puncture when performing caudal block. The anatomy of the lumbosacral area was evaluated using magnetic resonance imaging. In 2462 of the 2669 patients imaged, the dural sac terminal was located between the upper half of the 1st sacral vertebra and the lower half of the 2nd sacral vertebra. In 22 cases (0.8%), the dural sac terminal and the spinal canal were located at or below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 9 publications
1
34
3
1
Order By: Relevance
“…It has been reported that 61.2%-87% of patients who harbor TCs are women [5,6,30,48,50]. We found that this number was 74.8% in case reports and 90% in our EMG study.…”
Section: Prevalencesupporting
confidence: 61%
See 1 more Smart Citation
“…It has been reported that 61.2%-87% of patients who harbor TCs are women [5,6,30,48,50]. We found that this number was 74.8% in case reports and 90% in our EMG study.…”
Section: Prevalencesupporting
confidence: 61%
“…Previous studies that analysed the MRIs of patients with lower back pain have reported a prevalence of 1.5%-4.6% [6,22,48,49]. However, because lower back and leg pain are almost always attributed to lumbar degenerative changes or disc problems, these MRIs did not routinely include axial or coronal sequences of the sacrum.…”
Section: Prevalencementioning
confidence: 99%
“…The dural sac usually terminates between S1 and S2 vertebra, with the majority at S2 [8, 9, 15, 16]. In 1 to 5% of patients, the dural sac terminates at S3 or below [15, 16].…”
Section: Anatomymentioning
confidence: 99%
“…13,15) Therefore, we reviewed MR-based series of case reports dealing with five or more SMCs (Table 1). [1][2][3][4][6][7][8][9][10][11]13,15,[18][19][20] Our study identified at least 5 cases of multiple SMCs out of 10 cases. Amazingly, not only multiple but also large cysts in Group 3 were found in this study.…”
Section: Discussionmentioning
confidence: 97%
“…10) Recently, the prevalence of SMC was reported as 46/2669 (1.6%) in Korean adults with low back pain and/or sciatica. 8) Although the exact sequences were not described, conventional sagittal T 1 -and/or T 2 -weighted MR imaging was employed.…”
Section: Discussionmentioning
confidence: 99%